2022
DOI: 10.1093/sleepadvances/zpac001
|View full text |Cite
|
Sign up to set email alerts
|

Comparing polysomnography, actigraphy, and sleep diary in the home environment: The Study of Women’s Health Across the Nation (SWAN) Sleep Study

Abstract: Study Objectives Polysomnography (PSG) is considered the “gold standard” for assessing sleep, but cost and burden limit its use. Although wrist actigraphy and self-report diaries are feasible alternatives to PSG, few studies have compared all three modalities concurrently across multiple nights in the home to assess their relative validity across multiple sleep outcomes. This study compared sleep duration and continuity measured by PSG, actigraphy, and sleep diaries and examined moderation by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 70 publications
0
25
0
Order By: Relevance
“…Naively, this comparison seems to show some advantage to the DREEM, yielding smaller average biases from the sleep logs for all the wake‐related parameters (SOL, WASO, NoA) and smaller absolute biases for TST. However, it is well established that subjective self‐reports of sleep are often biased compared with PSG, with typical underestimation of WASO, overestimation of TST, and either overestimation or accurate estimation of SOL (Kaplan et al, 2012; Lehrer et al, 2022; McCall et al, 1995). Our data in Table 1 are consistent with this pattern for WASO but exhibit the typical overestimation of TST only when comparing the sleep logs with the Zmachine, and only show accurate estimation of SOL when comparing the sleep logs with the DREEM (when compared with the Zmachine, SOL was actually underestimated).…”
Section: Discussionmentioning
confidence: 99%
“…Naively, this comparison seems to show some advantage to the DREEM, yielding smaller average biases from the sleep logs for all the wake‐related parameters (SOL, WASO, NoA) and smaller absolute biases for TST. However, it is well established that subjective self‐reports of sleep are often biased compared with PSG, with typical underestimation of WASO, overestimation of TST, and either overestimation or accurate estimation of SOL (Kaplan et al, 2012; Lehrer et al, 2022; McCall et al, 1995). Our data in Table 1 are consistent with this pattern for WASO but exhibit the typical overestimation of TST only when comparing the sleep logs with the Zmachine, and only show accurate estimation of SOL when comparing the sleep logs with the DREEM (when compared with the Zmachine, SOL was actually underestimated).…”
Section: Discussionmentioning
confidence: 99%
“…Another potential source of misclassification relates to the lack of objective sleep assessment in the study. Subjective sleep reports tend to overestimate time in bed and sleep time, 46,47 and it is therefore likely that in some cases our tracking results are not strictly limited to the sleep period but might also include short wake periods before sleep onset and after awakening. While this seems negligible for most research questions, we suggest not to use our dataset to investigate research questions that require an unambiguous (objective) sleep onset time point.…”
Section: Collaborationmentioning
confidence: 99%
“…Lastly, most studies relied on self-reported measures of sleep, which can overestimate (e.g., sleep duration) or underestimate (e.g., wake after sleep onset) sleep in some domains. 25 Studies with objective measures of sleep using actigraphy can more accurately measure sleep health, which would further our understanding of the association between sleep health and GWG.…”
Section: Introductionmentioning
confidence: 99%